GUIDELINES FOR THE APPLICATION OF ELECTROTHERAPY AND LASER THERAPY IN BURN PATIENTS - Bezerra Batista, Juliana (Health and Society, 2024)
This article addresses the importance of electrotherapy and laser therapy in the treatment of burn patients, justifying their need due to the complexity involved in the recovery of these individuals and the recent advances in these therapeutic modalities. Burns cause deep damage to the skin and underlying tissues, generating complications such as intense pain, hypertrophic scars, and functional loss. Despite the conventional use of medications, grafts, and topical care, there is a growing demand for complementary treatments that accelerate healing, control pain, and promote more effective rehabilitation. The objective of this study is to review and analyze the effects of electrotherapy and laser therapy on the healing process, pain control, and functional recovery of burn patients. The methodology used was a literature review in scientific databases, including articles published between 2015 and 2023, focusing on research that examined the use of these therapies in the context of burns. The results indicate that electrotherapy favors tissue healing by increasing blood flow and stimulating cell regeneration, in addition to providing pain relief through transcutaneous electrical nerve stimulation (TENS). Laser therapy, in turn, accelerates healing by stimulating the production of ATP in cells, reducing inflammation and improving the quality of scars, minimizing the risk of hypertrophic scars and keloids. Studies that combine both therapies show a faster and more effective recovery, with a lower incidence of complications. The conclusion highlights that the combined application of electrotherapy and laser therapy presents significant benefits, being an effective alternative to optimize healing, reduce pain and improve the functionality of burn patients. Dissemination of these results is essential to improve clinical care and encourage future research that expands the use of these therapies in clinical practice.